Sistema para la gestión estratégica institucional: Módulo para el plan opertivo anual de la Universidad Técnica de Cotopaxi. - Puco Veloz, Jenny Carolina (2018)
The problem of managing information in a manual way allows time-wasting when managing activities and processes. In most public institutions have manual processes that generate delays in information delivery and generation of reports that the dependencies require, because they do not have a computer tool that allows to streamline their processes related to the annual operating plan for, for this reason the present technological proposal proposes to develop a method oriented to the management of data of four thematic axes such as training, linking, management, and research in the Planning Department of the Technical University of Cotopaxi located in the El Ejido neighborhood, San Felipe sector in the city of Latacunga, Cotopaxi Province. The methodology for the development of the system is SCRUM because it helps to work with the Iterative Incremental model allowing a suitable organization of the work during the whole development cycle through programming language .NET, SQL Server and an architecture that works with vista model and controller. As a result of the implementation of the Annual Operational Plan system, the biannual programming could be automated based on the evaluation of each project, resulting in a traffic signal for the user to more easily identify the efficiency and effectiveness of their programming, with this it was possible to reduce time in delivering reports of the different strategic axes. The implementation of this system will allow better administration processes in the department of the object of study.